1991
DOI: 10.1038/hdy.1991.55
|View full text |Cite
|
Sign up to set email alerts
|

Positional control of chiasma distribution in the house mouse. Chiasma distribution in mice homozygous and heterozygous for an inversion in chromosome 1

Abstract: An examination of the chiasma distribution in chromosome 1 of male mice homozygous and heterozygous for a distal inversion In( 1) 1 2Rkand in normal males was carried out. No differences in chiasma distribution were found between homozygotes for the inversion and homozygotes for normal chromosome 1. A significant decrease in the frequency of bivalents bearing chiasmata in the pretelomeric region was found in heterozygotes. This, in its turn, produced a redistribution of chiasmata in the proximal non-inverted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Gorlov and Borodin (1995) [ 43 ], for instance, showed that a large inversion had no effect on the global recombination rate. In an earlier study, the same authors had observed a reduction of recombination due to a decrease in the number of chiasmata in the inverted region [ 44 ]. In men, Kirkpatrick et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gorlov and Borodin (1995) [ 43 ], for instance, showed that a large inversion had no effect on the global recombination rate. In an earlier study, the same authors had observed a reduction of recombination due to a decrease in the number of chiasmata in the inverted region [ 44 ]. In men, Kirkpatrick et al .…”
Section: Discussionmentioning
confidence: 99%
“…Проксимальный (прицентро мерный) рекомбинаци онный пик был характерен для плеч акроцентрических хромосом черной крачки и отсутствовал в тех же пле чах, которые входили в состав мета центрической хромосомы у речной крачки. Это подтверждает предпо ложение о том, что паттерн распре деления рекомбинационных обменов в большей степени опреде ляется морфологией хромосомы, а не гене тическим со держанием отдельных ее районов (Gorlov et al, 1991).…”
Section: генетика животных вавиловский журнал генетики и селекции • 2unclassified
“…In ml 2/ + the frequency of the loops was much lower (36.8 per cent), and almost all of the loops were incomplete and contained large asynaptic and heterosynaptic zones. The rest of the nuclei contained only straight bivalents with heterosynapsis in the inverted regions (Borodin et al, 1 990a;Gorlov et al, 1991). In other words, in ml 2/ + males the population of cells in which chiasmata were able to arise in the regions of the inversion was rather restricted.…”
Section: Discussionmentioning
confidence: 99%